Pregnancy and protection: perceptions, attitudes and experiences of Australian female adolescents - Skinner, S; Smith, J.; Fenwick, J.; Hendriks, J.; Fyfe, S.; Kendall, Garth (Elsevier, 2009)
Background and purpose: Despite decades of research, development and evaluation of educational and promotional strategies to prevent teenage pregnancy, we have only a limited understanding of the strategies that are effective and why. This study sought to explore female teenagers' attitudes, perceptions and experiences of contraceptive use, and describe the influence of this on pregnancy risk.